Engaging the Future by Restructuring Expectations Steven D. Crow. - Crow, Steven D. (Distributed by ERIC Clearinghouse, 2002)
In this address, the Executive Director of The Higher Learning Commission ("Commission") shares his thoughts about the renovation of the Commission as it prepares for the future. The Commission is an organization of great integrity, which has worked for successful renewal in the past, and on this basis it will be possible to build the next project of the Commission, that of rewriting its accreditation standards. The Commission is aware that the standards it creates will not serve for the next century; it hopes they will be useful for the next decade. The leadership, commitment, and openness that are apparent in this renovation project give confidence that the standards that are developed will be the best they can be, and the Commission will be able to move on to new challenges, including reducing confidentiality in its future actions. (SLD)